Puerarin dry powder inhaler formulations for pulmonary delivery: Development and characterization. - Md Abdur Rashid; Saiqa Muneer; Tony Wang; Yahya Alhamhoom; Llew Rintoul; Emad L Izake; Nazrul Islam (PLoS ONE)
This study aims at developing and characterizing the puerarin dry powder inhaler (DPI) formulations for pulmonary delivery. The inhalable particles size (<2 μm) was accomplished by micronization and its morphology was examined by scanning electron microscopy (SEM). The puerarin-excipient interaction in powder mixtures was analyzed by using Fourier transform infrared spectroscopy (FTIR), Raman confocal microscopy, X-Ray powder Diffraction (XRD), and differential scanning calorimetry (DSC) methods. Using a Twin stage impinger (TSI), the in-vitro aerosolization of the powder formulations was carried out at a flow rate of 60 L/min and the drug was quantified by employing a validated HPLC method. No significant interactions between the drug and the excipients were observed in the powder formulations. The fine particle fraction (FPF) of the drug alone was 4.2% which has increased five to six-fold for the formulations with aerosolization enhancers. Formulation containing lactose as large carriers produced 32.7% FPF, which further increased with the addition of dispersibility enhancers, leucine and magnesium stearate (40.8% and 41.2%, respectively). The Raman and FTIR techniques are very useful tool for understanding structural integrity and stability of the puerarin in the powder formulations. The puerarin was found to be compatible with the excipients used and the developed DPI formulation may be considered as an efficient formulation for pulmonary delivery for the management of various diseases at a very low dose.